Nature-based solutions to increase sustainability and resilience of vineyard-dominated landscapes - Adrien Rusch (Basic and Applied Ecology)
Vineyards are highly intensive systems very often located in biodiversity hotspots at the global scale. These ecosystems are now facing major environmental, agronomical and economic issues that challenge their sustainability. Based on multiple evidence, I illustrate here how biodiversity and several nature-based solutions across scales, from manipulating within-field plant communities to landscape-scale diversification, can provide benefits related to key societal challenges that vineyard socio-ecosystems are facing. These findings support the idea that biodiversity and ecosystem services play a key role in the functioning of these landscapes and that nature-based solutions offer a sustainable pathway for the future of vineyard agroecosystems. This literature review also highlights several gaps of knowledge that define a research agenda for nature-based solutions to strengthen multifunctionality of vineyard landscapes.